Development of the foregut and the formation of the trachea and esophagus in rat embryos. A symphony of confusion - Ginzel, Marco; Huber, Nana; Bauer, Leopold; Kluth, Dietrich; Metzger, Roman (Frontiers in Cell and Developmental Biology, 2023)
Introduction: During embryonic development, the trachea emerges from an area of the foregut, which is often referred to as “anterior” or “common” foregut tube or simply foregut. To explain this process of differentiation, four competing models exist to date. The outgrowth and watershed models propose a foregut that remains constant in length. In the outgrowth model, the trachea buds off and elongates from the foregut, while in the watershed model, a mesenchymal wedge splits the growing foregut into the trachea and esophagus. In contrast, the septation model proposes a cranial splitting and thus a shortening of the “common” foregut tube into the trachea and esophagus by an emerging septum. Finally, the splitting and extension model describes an interaction of cranial splitting of the foregut and simultaneous caudal tracheal and esophageal growth. Methods: Here we examine the development of the undifferentiated foregut by micro computed tomography, which allows precise measurements. Results: Our results show that this area of the foregut transforms into the larynx, a process, which is independent from tracheal and esophageal development. Discussion: These observations are only consistent with the outgrowth model.